Synthetic Strategies to Serine-Proline Chimeras: An Overview - Ammazzalorso, Alessandra; De Filippis, Barbara; Maccallini, Cristina; Pierini, Marco (Current Bioactive Compounds, 2016)
This review focuses on synthetic strategies developed to obtain serine-proline chimeras. The conformational properties of proline, combined with functional groups typical of aminoacid side chains, represent an interesting approach to stabilize peptide secondary structures such as β-turns. Different chemical pathways to synthesize 3-, 4-, and 5-hydroxyprolines, considered proline chimeras of aminoacid serine, will be presented and discussed.
Keywords: serine